SYARI’AT ISLAM DAN PLURALITAS SOSIAL (Studi tentang Minoritas Non-Muslim dalam Qanun Syari’at Islam di Aceh) - Danial, Danial (Universitas Islam Negeri Raden Intan Lampung, 2012)
This article focuses on answering questions on the application of the principles of enforcement of Shari’a Qanun in Aceh, its position and its implications for non-Muslim minorities in the Shari’a Qanun. Based on indepth reviews of various laws and regulations, local regulations of Shari’a-Qanuns, and other relevant literatures, the author found that the Shari’a Qanuns imposed Islamic law in Aceh adhere to the principles of quasi personality. On one side, the Qanun is only valid for every Muslim who is in Aceh (the principles of personality), but on the other hand this also applies to any person resides in the territory of Aceh (the principle of territoriality), including those of non-Muslim minorities; in particular if they do offenses not provided in the book of penal law or in other regulations outside the book of penal law, such as seclusion (khalwat) and ikhtilat. Implementation of such Qanun thus potentially gives raise intolerance to human rights violations (Human Rights), as opposed to the 1945 Constitution which guarantees every citizen to profess and practice their believe and religion. The solution might be that the formulation of the Qanuns and its implementation in Aceh need to take several steps and considerations, including identification of a common platform that upholds the moral conception of justice, humanity and welfare.